VD_FINDINFO Jug / 2011 / 264 vom 29. Juni 2011 - VD Tribunal cantonal (2011)
FIXATION DE LA PEINE, PEINE PÉCUNIAIRE, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, FRAISEN GÉNÉRAL | 144 al. 1 CP, 34 CP, 47 CP, 425 CPP (CH), 426 al. 1 CPP (CH)